Czech Sci-fi Fanzines in the Era of Late Socialism and Early Post-socialism - Kudláč, Antonín (My University, 2020)
The fanzines have belong among the most significant communication means of the subculture of fans and „users“ of fantastic arts, the so called sci-fi (SF) fandom since its birth. This is also the case of Czechoslovak (later Czech and Slovak) fandom, in which the fanzines represented before all an activity of the SF clubs. The community of Czechoslovak fans mostly belonged to the „greyzone“ of late-socialist society, where the members of fandom were more or less tolerated. Czechoslovak SF fandom has changed to a formally organized structure after 1989, some of the existing SF fanzines disappeared and others became the basis for professional magazines or publishing houses; however, the traditional fanzines connected with SF clubs have continued. The fanzine production has gradually passed in to the sphere of digital publishing (e-zines / webzines) at the same time. Digitization of fanzine publishing clearly reflects the changes of SF fandom, which has been oscillating between social alternative and cooperation with cultural industry.
České sci-fi fanziny v éře pozdní normalizace a raného postkomunismu
Keywords: SF fanzines; SF fandom; participatory culture; late socialism; post-socialism; „greyzone“; sci-fi fanziny; sci-fi fandom; participační kultura; pozdní normalizace; raný postkomunismus; "šedá zóna"